Scientific and methodological foundations of the formation of football playing skills in middle school students - Izhanov, Zhomart; Seisenbekov, Yerlan; Seisenbekov, Yerlan; Kokebayeva, Rysgul; Abishev, Kendibay; Orazov, Shamurat; Tastanov, Adilbay (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study was conducted to develop and assess a new experimental football training program designed to engage students in football and enhance their skills, knowledge, and techniques related to football. The experimental training program (a combination of theory and practice) was assessed based on three elements of the program: teaching modules, practical coaching, and game competition. Based on the results, increasing practical coaching for football students further enhances their football skills. The relationship between game competition (GC) and students’ football skills development (SFSD) was significant (β = 0.929; p=0.000). Also, the relationship between experimental teaching and training program (ETTP) and football skills was significant (β =0.875; p=0.000). Therefore, football skills were developed with the program and the majority of students performed exceptionally well during and after the completion of the program. The results show that students’ performance increased significantly as compared to former theory-based models. Also, students’ level of engagement increased with the new experimental training program. The experimental training program was developed to overcome the weakness of the current football training program, which was lacking in skills development and student engagement.